A Glimpse into the Genetic Heritage of the Olive Tree in Malta - Monica Marilena Miazzi; Antonella Pasqualone; Marion Zammit-Mangion; Michele Antonio Savoia; Valentina Fanelli; Silvia Procino; Susanna Gadaleta; Francesco Luigi Aurelio; Cinzia Montemurro (Agriculture, 2024)
The genetic diversity of the ancient autochthonous olive trees on the Maltese islands and the relationship with the wild forms growing in marginal areas of the island (57 samples), as well as with the most widespread cultivars in the Mediterranean region (150 references), were investigated by genetic analysis with 10 SSR markers. The analysis revealed a high genetic diversity of Maltese germplasm, totaling 84 alleles and a Shannon information index (I) of 1.08. All samples from the upper and the lower part of the crown of the Bidni trees belonged to the same genotype, suggesting that there was no secondary top-grafting of the branches. The Bidni trees showed close relationships with the local wild germplasm, suggesting that the oleaster population played a role in the selection of the Bidni variety. Genetic similarities were also found between Maltese cultivars and several Italian varieties including accessions putatively resistant to the bacterium Xylella fastidiosa, which has recently emerged in the Apulia region (Italy) and has caused severe epidemics on olive trees over the last decade.